Cornerstones in Ulrich Bach's Work on Theology and Disability - Caspar, Cyril L. (Journal of religion, disability & health, 2011)
This article outlines the theological cornerstones of Ulrich Bach, a German theologian in the field of theology and disability. The present text aims at offering a general approach to Ulrich Bach's work for the English-speaking world by considering the christological, soteriological, and ecclesiological themes of his work. Moreover, this article includes some of the central passages of his work in translation.